2010
DOI: 10.1186/1471-2407-10-113
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo anticancer properties of a Calcarea carbonica derivative complex (M8) treatment in a murine melanoma model

Abstract: BackgroundMelanoma is the most aggressive form of skin cancer and the most rapidly expanding cancer in terms of worldwide incidence. Chemotherapeutic approaches to treat melanoma have had only marginal success. Previous studies in mice demonstrated that a high diluted complex derived from Calcarea carbonica (M8) stimulated the tumoricidal response of activated lymphocytes against B16F10 melanoma cells in vitro.MethodsHere we describe the in vitro inhibition of invasion and the in vivo anti-metastatic potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 37 publications
(44 reference statements)
0
28
0
1
Order By: Relevance
“…A recent study showing in vitro and in vivo anticancer properties of Calcarea carbonica derivative complex M8 (highly diluted natural product) in a murine melanoma model, demonstrated inhibition of tumor growth and metastasis by decrease in perlecan expression (component of basement matrix and its expression correlates strongly with the expression of several metastatic, angiogenic and invasive factors in tumor cells, particularly melanoma cells) and a direct inhibition of cancer cell adhesion and invasion. 22,23 Another study revealed that on treatment with a complex homeopathic medication (Calcarea carbonica CH5) there was an indirect activation of lymphocytes through their interaction with macrophages, even without direct cellecell contact. The co-culture of macrophages and lymphocytes in the presence of CH5 promoted immunostimulation of lymphocytes, resulting in enhanced tumoricidal performance against a very aggressive line of melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showing in vitro and in vivo anticancer properties of Calcarea carbonica derivative complex M8 (highly diluted natural product) in a murine melanoma model, demonstrated inhibition of tumor growth and metastasis by decrease in perlecan expression (component of basement matrix and its expression correlates strongly with the expression of several metastatic, angiogenic and invasive factors in tumor cells, particularly melanoma cells) and a direct inhibition of cancer cell adhesion and invasion. 22,23 Another study revealed that on treatment with a complex homeopathic medication (Calcarea carbonica CH5) there was an indirect activation of lymphocytes through their interaction with macrophages, even without direct cellecell contact. The co-culture of macrophages and lymphocytes in the presence of CH5 promoted immunostimulation of lymphocytes, resulting in enhanced tumoricidal performance against a very aggressive line of melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Guimarães et al attributed the anti tumoricidal effect of homeopathic preparations on their ability to prime the immune system to seek out and destroy cancer cells. 23 It is possible that in vivo ultra-diluted higher potencies alter the immune system resulting in enhanced cytotoxicity against cancer cells. But our in vitro study was based on homogenous cell populations, with no immune cell component.…”
Section: Discussionmentioning
confidence: 99%
“…14 This pre-clinical study presented here provides data supporting the efficacy of M1 for melanoma therapy. Using a method based on combinatory and high occurrence rates and low doses of M1 inhaled, as previously described, 15 we show for the first time that M1 treatment reduced the tumor burden of an experimental pulmonary metastasis model and primary tumor formation of mouse melanoma. In summary, we identified physiologic factors leading to the control of initial pathways of tumor metastasis and growth.…”
Section: Introductionmentioning
confidence: 94%
“…Solutions were vigorously homogenized and immediate applied to animals via oral inhalation as previously described. 15 Briefly, animals were placed into oral inhalation chambers and treated for 10 min, twice a day, 12 h apart for a period of 14 days. Following 15 days of cell inoculation, mice were anesthetized with 100 mg/kg ketamine (DopaleneVetbrands) and 20 mg/kg xilazin (AnasedaneVetbrands) followed by euthanasia by cervical dislocation.…”
Section: Experimental Pulmonary Metastasis Modelmentioning
confidence: 99%
“…In vivo C. carbonica (M8) diluent directly inhibits B16F10 murine melanoma cell adhesion and invasion, and inhibits melanoma growth and metastasis by decreasing perlecan (heparin sulfate proteoglycan 2 [HSPG2]) expression [4,20]. C. carbonica 6C produces 30% to 35% cancer cell apoptosis in Ehrlich's ascites carcinoma (EAC), Sarcoma-180 (S-180), MCF-7, MDA-MB-231, and HBL-100 breast cancer bearing Swiss albino mice, providing a survival advantage, p<0.001, by Student's t test [21].…”
Section: Homeopathic Cancer Treatmentsmentioning
confidence: 99%